ENAM Gene Mutation Factor in Amelogenesis Imperfecta - Anie Apriani; Linda Sari Sembiring; Ibnu Suryatmojo; Ferry Sandra (SONDE (Sound of Dentistry), 2018)
Amelogenesis Imperfecta (AI) is an abnormal disease that occurs in hard tissue of teeth. Clinical features of Amelogenesis Imperfecta look like immature enamel that looks like hypomaturation. The etiology of AI is influenced by the TGF-?1 factor which is disturbed during the formation and development of enamel, one of which is caused by the presence of ENAM gene mutations. Further research on genetic history in the family and biomineralization of the formation of enamel important to be developed later.